Integrated network pharmacology, metabolomics, transcriptomics and microbiome strategies to reveal the mechanism of Sang Ju Yin on the treatment of acute lung injury on the gut-microbiota-lung axis - Song Lin; Ruinan Ren; Fang Wang; Zilong He; Cuiyan Han; Jinling Zhang; Wenbao Wang; Jie Zhang; Huiyu Wang; Huimin Sui; Tianyang Wang (Arabian Journal of Chemistry, 2024)
Acute lung injury (ALI) is a clinically prevalent inflammatory disorder that still needs to be developed with more accurate diagnostic biomarkers and more satisfactory therapies. This study intended to explore the therapeutic material basis and molecular mechanisms of a classical traditional Chinese medicinal prescription, Sang Ju Yin (SJY), against ALI, focusing on the chemical components of formula composition, the disturbance of host genes/metabolites and the dysbiosis of intestinal flora. First, based on liquid chromatography-mass spectrometry (LC-MS) component analysis, 212 in vitro and 44 in vivo compounds were identified respectively in SJY. Then, network pharmacology was adopted to calculate potential anti-ALI compounds in SJY and predict that CXCR2, PI3K-Akt signaling and arachidonic acid (AA) metabolism could be potential targets. Subsequently, integrative multi-omics techniques were employed to elaborate deeper systematic molecular mechanisms. Metabolomic data combining both 1H NMR and LC-MS techniques illustrated that 146 pulmonary and 75 fecal biomarkers, associated with AA and other metabolisms, were recuperated by SJY’s intervention. Transcriptomic analyses suggested that SJY could significantly regulate genes and signaling pathways involved with inflammation and apoptosis, such as PI3K-Akt. Further the obtained key targets (IL-10, LCAT, CXCR2 and C5) were verified by qRT-PCR and their relative compound-target interaction were validated by molecular docking. Notably, the disturbance of intestinal microbial community (such as the abundance of Lactobacillus, etc.) was detected through 16S rRNA gene sequencing, that could be effectively reshaped by SJY. Collectively, our integrated work showed SJY could regulate the crosstalk of metabolite-target-pathway-microflora along the gut-microbiota-lung axis on the whole. Noteworthy, our study provided fundamental and new insights into how molecular networks connected different types of components, genes, metabolites, microbes and potential pathways to map an endogenous functional landscape for clinical ALI diagnosis and SJY application.